School of enlightenment: a vision to create a place where people can learn, help each other to serve the community and find peace through yoga and meditation - Adiba, Mehnaz Ahmed (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture in Architecture, 2014.